Radiation exposure in the environment of patients after application of radiopharmaceuticals - Sudbrock, F.; Boldt, F.; Kobe, C.; Hammes, J.; Eschner, W.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2009)
Aim: After therapeutical application of radionuclides the patient has to be regarded as a radioactive source. The radiation exposure differs from diagnostic nuclear medicine due to the amount of radioactivity and due to β-radiation. Measurements of photon dose rates were carried out and estimates of β-radiation outside the patient using Monte-Carlo methods. Calculations of maximum β-ranges in tissue were also performed. Detailed knowledge of the radiation exposure close to the patient is of major importance with respect to radiation protection of the staff. Method: Photon dose rates for 32 patients were determined after treatment with [131I]NaI and [131I]meta-iodobenzylguanidin, [32P]Na2HPO4, [90Y]Zevalin and [153Sm]EDTMP. Readings were taken immediately after application at eight distances. Results: For therapies with 131I photon dose rates amount to 2 mSv·h-1·GBq-1 close to the patient. Taking the typical activities of 3.7 GBq for thyroid carcinoma and up to 11 GBq for mIBG therapies into account this leads to a considerable radiation exposure of approximately 7.5 mSv/h and 20 mSv/h, respectively. At a distance of 2 m the dose rates fall to 1/100 compared to the vicinity. For 153Sm the maximum of 100 μSv·h-1·GBq-1 is significantly lower compared to therapies using radioiodine. After application of 32P or 90Y all photon dose rates are lower (>10 μSv·h-1·GBq-1) but in both cases high energy β-particles associated with high maximum ranges exceeding 1 cm in tissue have to be considered. Conclusion: The remarkable difference of the dose rates in the vicinity of the radioactive patient compared to readings at 2 m distance underlines the major importance of the distance for radiation protection. After application of nuclides emitting high energy β-particles their contribution outside the patient should be considered. For typical procedures in the patient's vicinty the radiation exposure of the personnel remains below the annual limit of 20 mSv.
Keywords: Radiation protection; radioiodine therapy; dose rate; dosimetry; Monte-Carlo method